Multicultural Education Management Based on the Life Character of Siblings - Pattipeilohy, Poltjes; Cindy, Agustin Hanivia; Pattiasina, Johan (Civiliza Publishing, Indonesia., 2025)
The background of this research begins with social life in Ambon City which has various ethnicities, religions, and cultures. This diversity often becomes a challenge as well as an opportunity in the world of education. SMA Negeri 3 Ambon is one of the schools that stands out because it prioritizes the local value of